An Analysis of Publication Productivity During Residency for 1506 Neurosurgical Residents and 117 Residency Departments in North America. Issue 4 (30th May 2018) - Khan, Nickalus R; Saad, Hassan; Oravec, Chesney S; Norrdahl, Sebastian P; Fraser, Brittany; Wallace, David; Lillard, Jock C; Motiwala, Mustafa; Nguyen, Vincent N; Lee, Siang Liao; Jones, Anna V; Ajmera, Sonia; et al.
Abstract: BACKGROUND: Bibliometrics is defined as the study of statistical and mathematical methods used to quantitatively analyze scientific literature. The application of bibliometrics in neurosurgery continues to evolve. OBJECTIVE: To calculate a number of publication productivity measures for almost all neurosurgical residents and departments within North America. These measures were correlated with survey results on the educational environment within residency programs. METHODS: During May to June 2017, data were collected from departmental websites and Scopus to compose a bibliometric database of neurosurgical residents and residency programs. Data related to authorship value and study content were collected on all articles published by residents. A survey of residency program research and educational environment was administered to program directors and coordinators; results were compared with resident academic productivity. RESULTS: The median number of publications in residency was 3; median h -index and Resident index were 1 and 0.17 during residency, respectively. There was a statistically significant difference in academic productivity among male neurosurgical residents compared with females. The majority of articles published were tier 1 clinical articles. Residency program research support was significantly associated with increased resident productivity ( P < .001). Scholarly activity requirements were not associated with increased resident academic productivity. CONCLUSION: This study represents the most comprehensive bibliometric assessment of neurosurgical resident academic productivity during training to date. New benchmarks for individual and department academic productivity are provided. A supportive research environment for neurosurgical residents is associated with increased academic productivity, but a scholarly activity requirement was, surprisingly, not shown to have a positive effect.